Penerapan Model Auditory, Intellectualy, Repetition (Air) untuk Meningkatkan Keterlibatan dan Hasil Belajar Siswa dalam Mata Pelajaran IPAS - Ilma Rizka Ramadhanti; Nasihudin Nasihudin; Ani Yanti Ginanjar (Mutiara Pendidikan dan Olahraga, 2026)
This study aims to improve student engagement and learning outcomes in the subject of Natural and Social Sciences (Ilmu Pengetahuan Alam dan Sosial / IPAS) through the implementation of the Auditory, Intellectually, Repetition (AIR) learning model in a fourth-grade elementary school class. The initial problem indicated that student engagement in learning was still low, at 37.5%, with learning mastery reaching only 33.3% and an average class score of 68.0, which did not meet the Minimum Mastery Criteria (KKM) of 75. Therefore, improvement efforts were needed through the implementation of a more active and student-centered learning model. This study employed a Classroom Action Research (CAR) approach conducted in two cycles, where each cycle consisted of planning, action, observation, and reflection stages. The research subjects were 24 fourth-grade students. Data collection techniques included observation of student engagement, learning outcome evaluation tests, field notes, and documentation. Student engagement data were analyzed using percentages, while learning outcomes were analyzed through mean scores and the percentage of classical learning mastery. The results showed a significant improvement in each cycle. In Cycle I, student engagement increased to 62.5%, with learning mastery reaching 54.17% and an average score of 74.29, although it had not yet achieved classical completeness. In Cycle II, student engagement increased to 87.5%, with learning mastery reaching 100% and an average score of 85.42. These improvements indicate that the implementation of the AIR model was able to gradually and sustainably enhance both the learning process and outcomes. Based on these findings, it can be concluded that the Auditory, Intellectually, Repetition (AIR) learning model is effective in improving student engagement and learning outcomes in IPAS. This model can serve as an alternative learning strategy to create a more active, systematic, and student-centered learning environment.